2022
DOI: 10.1108/jfrc-04-2021-0037
|View full text |Cite
|
Sign up to set email alerts
|

Does risk governance mediate the impact of governance and risk management on banks’ performance? Evidence from a selected sample of Islamic banks

Abstract: Purpose Relying on the agency theory and the financial intermediation theory, the purpose of this paper is to examine to what extent risk governance would improve corporate governance and risk management effectiveness. The paper especially investigates the mediating role that would have the risk governance mechanisms in explaining both of the following relationships: the corporate governance–the banks’ performance, and the risk management–the banks’ performance. Design/methodology/approach This research uses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…El-Chaarani et al (2022) found that corporate-governance criteria have a positive and significant effect on the financial performance of banks. In addition, Jallali and Zoghlami's (2022) findings illustrated that risk governance expresses the relationship between corporate governance and bank performance, and they also found that internal corporate-governance mechanisms can improve company performance better than external ones. Marina and Lagasio (2022) found that board and committee independence can increase bank solvency, but board and committee size can decrease it.…”
Section: The Quality Of Corporate-governance Mechanisms and Bank Agilitymentioning
confidence: 92%
“…El-Chaarani et al (2022) found that corporate-governance criteria have a positive and significant effect on the financial performance of banks. In addition, Jallali and Zoghlami's (2022) findings illustrated that risk governance expresses the relationship between corporate governance and bank performance, and they also found that internal corporate-governance mechanisms can improve company performance better than external ones. Marina and Lagasio (2022) found that board and committee independence can increase bank solvency, but board and committee size can decrease it.…”
Section: The Quality Of Corporate-governance Mechanisms and Bank Agilitymentioning
confidence: 92%
“…[45,46], and bank profitability [47,48], this topic has been researched for a long time and is still developing today. A topic that has been around for a long time but has just started to be used frequently is risk corporate governance in Islamic Finance [49,50], performance measurement [9,51] and risk assessment [5,42] of Islamic Finance compared to conventional banks. In 2019-2020, research began to develop by comparing the Islamic financial system with other financial institutions [52].…”
Section: Fig 6 Abstract Co-occurrencementioning
confidence: 99%
“…Those self-disciplined standards can be summarized as corporate governance mechanisms, whose eventual goal is to mitigate agency problems (Dey, 2008) and to protect shareholders. In addition, because complex organizations suffer compliance difficulties because of developed priorities and information silos (Martinez, 2020), the internal mechanisms may work better than the external ones (Jallali and Zoghlami, 2022).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%